Toward Systematic Understanding of Flower Bud Induction in Apple: A Multi-Omics Approach - Milyaev, Anton; Kofler, Julian; Klaiber, Iris; Czemmel, Stefan; Pfannstiel, Jens; Flachowsky, Henryk; Stefanelli, Dario; Hanke, Magda-Viola; Wünsche, Jens-Norbert (Frontiers in Plant Science, 2021)
Flower bud induction in apple (Malus domestica Borkh.) is tightly connected to biennial bearing, which is characterized by alternating years with high (ON) and low (OFF) crop loads. In order to study this irregular cropping behavior, spur buds from ON- and OFF-trees of the biennial bearing cultivar ‘Fuji’ and the regular bearing cultivar ‘Gala’ we collected to precisely determine the time of flower initiation. Moreover, the physiological and molecular mechanisms leading to this event were evaluated over four weeks by a multi-omics approach, including RNA sequencing, proteomic and metabolic profiling. Gene and protein enrichment analysis detected physiological pathways promoting and inhibiting flower bud initiation. The results suggest that thiamine, chlorogenic acid and an adenine derivative are involved in early flower bud development. Tryptophan showed higher abundance in spur buds collected from ON-trees than those from OFF-trees. Cultivar comparison indicated that chlorogenic acid was more abundant in ‘Gala’ than in ‘Fuji’ spur buds, whereas the opposite was found for tryptophan. Genes controlling tryptophan biosynthesis were not affected by ON- and OFF-treatments but genes assigned to the metabolism of tryptophan into idoleacetate were differentially expressed between cultivars and treatments. The multi-omics approach permitted analyzing complex plant metabolic processes involved in flower bud induction and tracing some pathways from gene-to-product level.